"You've got to breathe, you know" – asthma patients and carers' perceptions around purchase and use of asthma preventer medicines. (6th February 2019) - Davis, Sharon R.; Tudball, Jacqueline; Flynn, Anthony; Lembke, Kirsty; Zwar, Nicholas; Reddel, Helen K.
Abstract: Objective : To explore influences on patients' purchase and use of asthma preventer medicines and the perceived acceptability of financial incentives via reduced patient co‐payments. Methods : Semi‐structured telephone or face‐to‐face interviews were conducted with adults and carers of children with asthma. Interviews were recorded, transcribed verbatim and coded. Data were analysed using thematic analysis via grounded theory. Results : Twenty‐four adults and 20 carers for children aged 3–17 years with asthma were interviewed. For medicines choice, most participants did not consider themselves the primary decision‐maker; cost of medicines was an issue for some, but effectiveness was described as more important. For adherence, cost, side‐effects, perceived benefit and patient behaviours were important. Conclusions : Patient barriers to adherence with asthma preventer medicines including cost are ongoing. Healthcare professionals need to encourage empathic discussion with patients about cost issues. Implications for public health : Asthma patients and carers could benefit from greater involvement and respect within shared decision‐making. Healthcare professionals should be aware that cost may be a barrier for patient adherence, and provided with information about the relative costs of guideline‐recommended asthma medicines. Patients and healthcare professionals need education around the efficacy of ICS‐alone treatment and the rationale behind co‐payments, for initiatives around quality use of medicines to succeed.